ANALISIS PENERAPAN NEARLY ZERO EMISSION BUILDING DALAM UPAYA MENGURANGI EMISI KARBON PADA SEKTOR BANGUNAN (Analysis of the Implementation of Nearly Zero Emission Buildings Efforts to Reduce Carbon Emissions in the Building Sector) - Chandra Budiman; Agung Cahyo Nugroho; Fadhilah Rusmiati (Tesa Arsitektur, 2024)
Indonesia's urbanization issue ranks fourth in Southeast Asia. Urbanization correlates with a 1% increase in emissions for every 1% increase in the population. In the building sector, this trend will increase the demand for building construction, impacting building resources such as power plants (energy sector). The energy sector contributes the highest carbon emissions at 94.64%. This rise in carbon emissions can hinder the goal of reducing emissions by 29% by 2030. The Nearly Zero Emission Building (NZEB) approach is proposed as a solution for energy efficiency. The NZEB approach involves steps during the pre-construction phase using passive strategies and post-construction with active strategies through building operations to reduce building energy needs. This research uses a qualitative method based on three standards from three countries with different climates to review the implementation results. The analysis results show three strategies: passive strategies (orientation, natural lighting, and ventilation), active strategies (Building Management Systems (BMS), renewable energy use, and building materials), and alignment with Green Building to maximize this approach. In Indonesia, alignment with the Green Building Council Indonesia (GBCI) is necessary. GBCI has designed Greenship "Net Zero," focusing on assessments such as air quality, natural openings, and carbon emission reduction calculations. This will help quantitatively reduce carbon emissions in the building sector.